Enhanced accumulation of microalgal pigments using metal nanoparticle solutions as light filtering devices - Eroglu, Ela; Eggers, P.; Winslade, M.; Smith, S.; Raston, C. (2013)
Localized surface plasmon resonances of various metal nanoparticles are used as wavelength specific backscattering light filters. Placing spheroidal silver nanoparticles and gold nanorods around microalgal culture flasks increased the formation of photopigments in Chlorella vulgaris microalgal cells by such backscattering in the spectral regions favourable for microalgal growth. © 2013 The Royal Society of Chemistry.